The tide knot - Dunmore, Helen, 1952- (London : HarperCollins, 2012)
Two years after the disappearance of their father, Sapphire and Conor, having moved with their mother to the town of St. Pirans, try to make a new life for themselves, but Sapphire, unlike her mother and brother, finds it increasingly difficult to adjust to her new circumstances and is drawn more and more to the undersea world of Ingo.
6.0
5-8.
5-8
Keywords: Brothers and sisters -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Mermaids -- Juvenile fiction; Mermen -- Juvenile fiction; Brothers and sisters -- Fiction; Interpersonal relations -- Fiction; Mermaids -- Fiction; Mermen -- Fiction; Interpersonal relations -- Fiction; Mermaids and mermen -- Fiction; Siblings -- Fiction; Cornwall (England : County) -- Juvenile fiction; England -- Juvenile fiction; Cornwall (England : County) -- Fiction; England -- Fiction; Cornwall (England : County) -- Fiction; England -- Fiction